2014
DOI: 10.5625/lar.2014.30.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics approach to serum biomarker for loperamide-induced constipation in SD rats

Abstract: Loperamide has long been known as an opioid-receptor agonist useful as a drug for treatment of diarrhea resulting from gastroenteritis or inflammatory bowel disease as well as to induce constipation. To determine and characterize putative biomarkers that can predict constipation induced by loperamide treatment, alteration of endogenous metabolites was measured in the serum of Sprague Dawley (SD) rats treated with loperamide for 3 days using 1H nuclear magnetic resonance (1H NMR) spectral data. The amounts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Alterations in endogenous metabolites were also examined in the serum of Lop-induced constipation rats. Among 35 endogenous metabolites, four amino acids (alanine, glutamate, glutamine and glycine) and six endogenous metabolites related to the glycolysis pathway (acetate, glucose, glycerol, lactate, succinate and taurine) were dramatically decreased after Lop treatment [ 52 ]. These results provide a possibility that Urd can rescue the Lop-induced constipation by interfering with the balance of metabolites because Urd plays a role in the glycolysis pathway of galactose [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in endogenous metabolites were also examined in the serum of Lop-induced constipation rats. Among 35 endogenous metabolites, four amino acids (alanine, glutamate, glutamine and glycine) and six endogenous metabolites related to the glycolysis pathway (acetate, glucose, glycerol, lactate, succinate and taurine) were dramatically decreased after Lop treatment [ 52 ]. These results provide a possibility that Urd can rescue the Lop-induced constipation by interfering with the balance of metabolites because Urd plays a role in the glycolysis pathway of galactose [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies previously reported that inhibition of acetate and acetyl‐CoA carboxylase may lead to the accumulation of long‐chain acyl‐CoA, resulting in inadequate carbohydrate metabolism (Viola et al, ). Similarly, succinate is an intermediate in the TCA cycle and its decrease in concentration, though yet to reach statistical significance, also signals that TCA cycle is downregulated (Kim et al, ). We thus postulate the decrease of acetate in MA‐exposed rats can debilitate the TCA cycle, demonstrating MA exposure may disrupt energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is a chronic gastrointestinal disorder caused by various factors including insufficient dietary fiber intake, inadequate fluid intake, decreased physical activity, side effects of medication, hypothyroidism, and obstruction caused by colorectal cancer [ 19 ]. Recently, many studies have focused on investigation of the basic causes, development of novel therapeutic drugs and identification of molecular mechanisms responsible for constipation [ 20 21 23 ]. In an effort to investigate the molecular mechanisms associated with this disease, we investigated the role of Lop as an ER stressor, as well as the correlation between ER stress response and the laxative effect of L. platyphylla .…”
Section: Discussionmentioning
confidence: 99%